The variability of ruthenium in chromite from chassignite and olivine‐phyric shergottite meteorites: New insights into the behavior of PGE and sulfur in Martian magmatic systems. (27th November 2016) - Baumgartner, Raphael J.; Fiorentini, Marco L.; Baratoux, David; Ferrière, Ludovic; Locmelis, Marek; Tomkins, Andrew; Sener, Kerim A.
Abstract: The Martian meteorites comprise mantle‐derived mafic to ultramafic rocks that formed in shallow intrusions and/or lava flows. This study reports the first in situ platinum‐group element data on chromite and ulvöspinel from a series of dunitic chassignites and olivine‐phyric shergottites, determined using laser‐ablation ICP‐MS. As recent studies have shown that Ru has strongly contrasting affinities for coexisting sulfide and spinel phases, the precise in situ analysis of this element in spinel can provide important insights into the sulfide saturation history of Martian mantle‐derived melts. The new data reveal distinctive differences between the two meteorite groups. Chromite from the chassignites Northwest Africa 2737 (NWA 2737) and Chassigny contained detectable concentrations of Ru (up to 160 ppb Ru) in solid solution, whereas chromite and ulvöspinel from the olivine‐phyric shergottites Yamato‐980459 (Y‐980459), Tissint, and Dhofar 019 displayed Ru concentrations consistently below detection limit (<42 ppb). The relatively elevated Ru signatures of chromite from the chassignites suggest a Ru‐rich ( 1–4 ppb) parental melt for this meteorite group, which presumably did not experience segregation of immiscible sulfide liquids over the interval of mantle melting, melt ascent, and chromite crystallization. The relatively Ru‐depleted signature of chromite and ulvöspinel from the olivine‐phyric shergottites may be the consequence of relatively lower Ru contents (<1 ppb) in the parental melts, and/or the presence of sulfides during the crystallization of the spinel phases. The results of this study illustrate the significance of platinum‐group element in situ analysis on spinel phases to decipher the sulfide saturation history of magmatic systems.